Molecular genetic characterization and meat-use functional gene identification in Jianshui yellow–brown ducks through combined resequencing and transcriptome analysis - Li, Xinpeng; Xin, Aiguo; Ma, Li; Gou, Xiao; Fang, Suyun; Dong, Xinxing; Ni, Bin; Tang, Lin; Zhu, Li; Yan, Dawei; Kong, Xiaoyan (Frontiers in Veterinary Science, 2023)
The Jianshui yellow-brown duck is a unique country-specific waterfowl species in Yunnan Province, well known for its tender meat. However, there is a lack of comprehensive systematic research on the molecular genetic characteristics, especially germplasm resources and economic traits, of the Jianshui yellow-brown ducks. This study investigated the molecular genetic characteristics of Jianshui yellow-brown ducks, compared their selection signals with those of ancestral mallard and meat-type Pekin ducks, and identified genes specific to their meat-use performance. Furthermore, this study also evaluated the breeding potential for its meat performance. In this study, phylogenetic trees, PCA and Admixture analysis were used to investigate the population genetic structure among local duck breeds in China; population genetic differentiation index (Fst), nucleotide diversity and Tajima's D were used to detect selected loci and genes in the population of Jianshui yellow-brown ducks; and transcriptome technology was used to screen for differentially expressed genes in the liver, sebum and breast muscle tissues, and finally, the results of the genome selection signals and transcriptome data were integrated to excavate functional genes affecting the meat performance of the Jianshui yellow-brown ducks.The results of the genetic structure of the population showed that Jianshui yellow-brown ducks were clustered into a separate group. Selection signal analysis indicated significant selection pressure on certain genes related to meat characteristics (ELOVL2, ELOVL3, GDF10, VSTM2A, PHOSPHO1 and IGF2BP1) in both Jianshui yellow-brown ducks and mallards. Transcriptomic data analysis suggested that ELOVL3, PHOSPHO1 and GDF10 are vital candidate genes influencing meat production and quality in Jianshui yellow-brown ducks. A comparison of This is a provisional file, not the final typeset article selection signals between Jianshui yellow-brown ducks and Pekin ducks revealed only 21 selected genes in the Jianshui yellow-brown duck population, and no significant genes were related to meat traits. Moreover, whole-genome resequencing data suggested that the Jianshui yellow-brown duck represents a unique category with distinct genetic mechanisms. Through selection signaling and transcriptomic approaches, we successfully screened and identified important candidate genes affecting meat traits in Jianshui yellow-brown ducks. Furthermore, the Jianshui yellow-brown duck has good potential for improved meat performance, highlighting the need for further improvement.